Getting What We Pay For (and Other Unintended Consequences): An Overview of Federal Agricultural Policy - Hayes, MaryAnn (Maine Policy Review, 2011)
The reauthorization of the Federal Farm Bill in 2012 means that activity is heating up to reform U.S. agricultural, nutrition, and energy policy. Mary Ann Hayes provides an overview of the Farm Bill’s history, its intended and unintended consequences, and what can be hoped for in 2012.
Keywords: Federal farm bill; Federal agriculture policy; energy and food policy